Measuring Dietary Iron Absorption From Edible Tenebrio molitor and Assessing the Effect of Chitin on Iron Bioavailability: A Stable Iron Isotope Study in Young Women. (7th June 2021) - Hilaj, Nikolin; Galetti, Valeria; Lima, Roberta Murad; Krzystek, Adam; Andlauer, Wilfried; Zeder, Christophe; Zimmermann, Michael; Moretti, Diego
Abstract: Objectives: Iron deficiency is estimated to affect up to 1.5–2 billion people worldwide. Edible insects can be a rich source of iron and may have a smaller environmental food print than other animal source foods. Mealworm ( Tenebrio molitor ) larvae are recognized as an edible insect, but iron bioavailability in humans has not been investigated. Chitin, a major component of insect biomass, is a known iron binder. Our primary objective was to measure fractional iron absorption (FIA) from T.molitor with and without chitin in young women. Secondly, we aimed to assess the effect of the presence of mealworm biomass on iron absorption from iron present in low-phytate maize porridge. Methods: Non-anemic females (18–45 years, body weight < 65 kg) were recruited and FIA was measured as erythrocyte incorporation of stable isotopes tracers in red blood cells 14 days after test meal administration. Using a randomized cross over design, three different meals were administered to each subject, consisting of A) a low phytate refined maize porridge with 54 FeSO4 ; B) intrinsically labelled ( 57 Fe) T.molitor with native chitin and extrinsic 58 FeSO4 ; C) intrinsically labelled ( 57 Fe) T.molitor with reduced chitin and extrinsic 58 FeSO4 . Results: Median serum ferritin concentration in the participating subjects (n = 21) was 22.7 µg/L. Iron content in T.molitor larvae was FIA from meals B ( 58 Fe, 5.28%) and C ( 58 Fe, 4.55%) in which mealworm biomass was given in combination with maize porridge did not significantly differ to FIA from maize porridge fed alone (5.84%). In case of intrinsic labelling, FIA from meals B ( 57 Fe, 4.11%) and C ( 57 Fe, 4.03%) were significantly lower compared to maize meal A (P < 0.001). Conclusions: FIA from T.molitor was similar to low-phytate containing maize. Presence of mealworm biomass did not enhance or inhibit the FIA of iron present in the maize meal. Furthermore, a chitin reduction process did not show any discernible effect on FIA. T.molitor larvae could be a viable source of iron in the human diet, but iron absorption may be similar to plant-based foods. The study was registered at clinicaltrials.gov as NCT04510831. Funding Sources: Coop Research Program, World Food System Center, ETH Zurich, Switzerland.